Analysis of attack techniques of highly skilled female karatekas with hearing impairments - Ianchuk, K.; Tykhorskyi, O.; Petrenko, I. (Slobozhanskyi herald of science and sport, 2020)
Purpose: to determine the frequency of kicks by highly qualified female karatekas with hearing impairments, as well as their effectiveness. Material and Methods: the method of video recording and the method of analysis of literary sources were used in the study. The performance of 8 female athletes in 8 duels was investigated, 276 attacking actions were analyzed. Results: it was found that high-skilled karate athletes most often use Jodan (top-level, head-on) kicks, followed by Jodan kicks in the second place; Jodan kicks hitting the target (7.2% of the target) bring Ippon to the athlete which means 3 points, while Yuko (1 point) hits 17.27% of the target. The average time between strikes is 4.7 seconds, however, most of the time between strokes is from 1 to 3 seconds. Conclusions: optimization of individual training of highly qualified female karatekas can be done by changing the proportion of kicks in the way of increasing amount of kicks in the upper sector (Jodan), at the cost of kicks in the middle sector (Chudan), which according to the study are the least effective.